Dynamic centralized control and intelligent load management system of a remote residential building with V2H technology. (1st August 2022) - Elkholy, M.H.; Metwally, Hamid; Farahat, M.A.; Nasser, M.; Senjyu, Tomonobu; Lotfy, Mohammed Elsayed
Abstract: Energy is the main engine and the active element for all growth and development. It is the basic element for all sectors of the economy and a companion to human life. It is also not forgotten that most of the energy used in the whole world is traditional and unsustainable energy, as well as polluting the environment and causing harmful emissions. Sustainable is based primarily on environmental protection. Massive population growth is accompanied by a significant increase in energy consumption. Currently, most countries are turning to rely mainly on renewable energy sources. To achieve the maximum benefit from the energy, the tendency is to manage energy within the home to avoid the occurrence of energy losses. In this paper, an efficient home energy management system (HEMS) is proposed. This system is based on the use of a field-programmable gate array (FPGA) for home energy management. The proposed HEMS takes into account both generation and consumption as FPGA manages the feeding process through the sources. The prototype is implemented using Altera Cyclone IV EP4CE6 FPGA board using QUARTUS II software. The home is fed through PV, wind and fuel cells (FC) sources. If there is a shortage in energy production and the three sources are unable to cover the loads, the batteries enter into service to cover this shortage. If the sources and batteries are unable to cover the required loads, the EV contributes to covering the load, but with specific constraints set by the owner. The proposed HEMS works to control the feeding of the loads, as it schedules the feeding of the loads according to priority in the event of severe energy shortages and the inability of the sources, batteries and the EV to cover the loads. The experimental and simulation results proved the ability of the proposed system to respond to the demand by managing high energy-consuming household appliances according to the pre-set priority. Highlights: This study proposes the use of new technology for HEM through the use of the FPGA board. The proposed HEMS proves the high efficiency and reliability in managing energy flow from the three sources to the home. The proposed HEMS succeeds in reducing the execution time. The proposed HEMS system supports Vehicle-to-Home (V2H) approach with high efficiency.